A construção de consensos em conflitos socioambientais como instrumento de gestão ambiental integrada da região do Cocó em Fortaleza/CE - Sales, Alessander Wilckson Cabral (2017)
The current conflict over the use of sensitive, environmentally, economically, culturally and socially sensitive environments in densely populated urban areas has increased considerably as tensions between different views of different sectors of society grow. In view of this, it is necessary to discuss the most appropriate way of constructing its socio-environmental sustainability parameters. Fortaleza, capital of Ceará State, has an area with all these characteristics: densely inhabited, with high economic value and full of noble ecosystems and lush landscapes. This region of the city, known as Cocó, counts on the consensus of the society on the necessity of its preservation. The purpose of this thesis is to undertake an environmental, patrimonial and legal characterization of this region, to identify the conflicts in it and to categorize them, proposing an efficient systematics designed to better understand, compose and overcome them. To do so, it undertakes an analysis of conflict theory to define the most important socio-environmental conflicts in the area of study, and then analyzes the inadequacy of the traditional methods - basically consistent in the judicialization - of the composition of this special type of conflict, which only Has resulted in the intensification of litigiousness and the production of distributive injustices. The conflicts in the region studied, given their specific typology, due to their complexity and multiple stakeholders, require a consensual composition, through the use of the consensus building mechanism, capable of generating agreements that support the decision making process. From the democratic formulation of public policies of integrated environmental management for the region. Consensus building techniques, put into practice at the Cocó Forum, have demonstrated effective gains in the consolidation of consensual proposals formatted in cooperation with the various actors previously antagonistic, overcoming, as efficiency, conflicts that prevent the competent authority from realizing the protection So expected for the area studied. The efficiency found also recommends that the mechanism of consensus building, so successfully used in the concrete case of this thesis, be improved and its use be disseminated in the formulation of other important public policies, especially those of a social and environmental nature.